Liquidity Provision and the Cross Section of Hedge Fund Returns - Jame, Russell (Management Science, 2018)
I investigate whether hedge funds that supply liquidity earn superior returns. Using transaction data, I find that hedge funds following short-term contrarian strategies (i.e., liquidity suppliers) earn significantly higher returns on their equity trades and holdings. Similarly, using commercial databases, I find that hedge funds with greater exposure to a liquidity provision factor earn significantly higher excess returns and Sharpe ratios. The superior performance of liquidity-supplying hedge funds arises from strategies that are more complex than mechanical short-term reversal strategies. For example, among stocks with similar past returns, liquidity-supplying funds are more likely to trade against stocks heavily traded by constrained mutual funds and less likely to trade against stocks heavily traded by unconstrained mutual funds. The outperformance of liquidity-supplying funds is also concentrated in periods of low funding liquidity, suggesting that less-binding financial constraints contribute to their superior returns. The Internet appendix is available at https://doi.org/10.1287/mnsc.2016.2687 This paper was accepted by Lauren Cohen, finance.